2012
DOI: 10.1007/s00449-012-0738-9
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic granulation and nitrogen removal with the effluent of internal circulation reactor in start-up of a pilot-scale sequencing batch reactor

Abstract: Aerobic granular sludge was successfully cultivated with the effluent of internal circulation (IC) reactor in a pilot-scale sequencing batch reactor (SBR) using activated sludge as seeding sludge. N removal was investigated in the start-up of aerobic granulation process. Initially, the phenomenon of partial nitrification was observed and nitrite accumulation rates (NO(2) (-)-N/NO (x) (-) -N) were between 84.6 and 99.1 %. It was potentially caused by ammonium oxidizing bacteria (AOB) in the seeding activated sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…But only in recent years there have been more research facilities that reported the purification of real wastewater using aerobic granules [9][10][11][12][13]. Yet only few studies are known, that used aerobic granules in pilot scale either for treating municipal wastewater [14], soy protein wastewater [15], abattoir wastewater [16], synthetic low strength wastewater [13] or, swine slurry [17]. The benefits of aerobic granules are obvious: the entire process chain of carbon, nitrogen and phosphorus removal can be organized in one reactor at significant higher biomass concentrations compared to activated sludge systems.…”
Section: Introductionmentioning
confidence: 96%
“…But only in recent years there have been more research facilities that reported the purification of real wastewater using aerobic granules [9][10][11][12][13]. Yet only few studies are known, that used aerobic granules in pilot scale either for treating municipal wastewater [14], soy protein wastewater [15], abattoir wastewater [16], synthetic low strength wastewater [13] or, swine slurry [17]. The benefits of aerobic granules are obvious: the entire process chain of carbon, nitrogen and phosphorus removal can be organized in one reactor at significant higher biomass concentrations compared to activated sludge systems.…”
Section: Introductionmentioning
confidence: 96%
“…granular sludge for biological nitrogen removal. It is well accepted that the composition of granular microbial communities, including heterotrophic, aerobic bacteria grown on the outside, ammoniumoxidizing bacteria in the middle and facultative and anaerobic bacteria in the core of the granules [29]. Therefore, the outside heterotrophic bacteria are more sensitive than ammonium-oxidizing bacteria to the toxic environment.…”
Section: Methodsmentioning
confidence: 99%
“…It is considered to be an environment-friendly and cost effective technology for a full-scale biological application in the future (Wei et al, 2012). Compared to conventional activated sludge, aerobic granular sludge has excellent settling property, compact microbial structure and ability to withstand shock loadings (Adav et al, 2008).…”
Section: Introductionmentioning
confidence: 99%